Uji Aktivitas Antioksidan Ekstrak Daun dan Kulit Labu Air (Lagenaria siceraria (Molina) Standl.) - Masrifah, Masrifah; Rahman, Nurdin; Abram, Paulus H. (Universitas Tadulako, 2017)
The aim of the study was to determine the inhibitory concentration (IC50) of free radicals on an extract of calabash’s leaves and skins. The sample used in this study was the extract of calabash’s leaves and skins that made of 100 mg/L concentration. Determination inhibitory concentration of free radicals after adding DPPH (2,2-diphenyl-1-picrylhydrazyl) on the samples was determined using UV-Vis spectrophotometry. Concentration variations in leaves and skins extract of calabash used was 5, 10, 15 and 20 mg/L. The positive control used a vitamin C solution with a concentration that identical to the concentration of sample 5, 10, 15 and 20 mg/L. In the other hand, the negative control used a DPPH solution that was dissolved in ethanol p.a. The results showed that the leaves and skins extract of calabash with control of vitamin C have a concentration inhibition of free radicals (IC50) respectively was 9.268 mg/L (leaf extract), 9.332 mg/L (skin extract) and 6.839 mg/L (Vitamin C). The matter it was indicated that leaves and skins extract of calabash was a powerfully natural antioxidant.